Trajectories and Expectations in China. A Decentered Approach to Spanish International Mobility - Amelia Sáiz López (Migraciones, 2017)
The decade of 2010 has awakened the research interest in emerging flows of qualified young people towards Europe and Latin America. Spanish international migration is not exhausted in these destinations. A decentralized approach allows studying the Spanish residents in Shanghai, elaborating a typology from the perspective of mobilities where processes analyzed separately in previous migration studies converge. The complexity of mobility is not only explained by the geographical or labor dimensions. Based on in-depth interviews, the proposed qualitative analysis shows the need to cross-link all dimensions involved in individual and collective decision-making and the different strategies, within a given gender system, and according to objectives, social and family positions, resources and capital, in the context of globalization.